Respiratory distress and tracheal deviation secondary to sigmoid volvulus : A case report (International Journal of Medical and Surgical Sciences, 2022)
Introduction: The trachea is a semiflexible tube of 1.5 to 2 cm in width and 10 to 13 cm in length. Its deviation might be caused by not only diverse thoracic but also abdominal pathologies, which may compromise the airway. We present a case of a severe tracheal deviation due to an abdominal pathology causing displacement of mediastinal structures.Clinical Case: A 78-year-old woman presents with difficulty breathing. History of chronic bedridden and frequently constipated, last stool 5 days prior. On physical examination, cachectic complexion, dry mucous membranes, breathing superficially with scarce wheezing, SatO2 82% on room air. Abdomen distended with an absence of bowel sounds. Chest x-rays show severe tracheal deviation and abdominal x-ray with coffee bean sign. A laparotomy evidences a large sigmoid volvulus. A sigmoidectomy and descending colon colostomy is performed. Room air oxygen saturation improved after extubation to 96%.Conclusion: Desaturation and tracheal deviation were caused by a large sigmoid volvulus. Although these pathologies were thoracic, clinicians should suspect different underlying pathologies, in this case, abdominal.
Keywords: Intestinal volvulus; trachea; Respiratory Distress Syndrome